Conditional dominance in games with unawareness - Martin Meier; Burkhard Schipper (University of California, Department of Economics, 2022)
Heifetz, Meier and Schipper (2013) introduced generalized extensive-form games that allow for asymmetric unawareness. Here, we study the normal form of a generalized extensiveform game. The generalized normal-form game associated to a generalized extensive-form game with unawareness may consist of a collection of normal-form games. We use it to characterize extensive-form rationalizability (resp. prudent rationalizability) in generalized extensive-form games by iterative conditional strict (resp. weak) dominance in the associated generalized normal-form. We also show that the analogue to iterated admissibility for generalized normal-form games is not independent of the extensive-form structure. This is because under unawareness, a player's information set not only determines which nodes he considers possible but also of which game tree(s) he is aware of.
Keywords: C72; D83; 330; Awareness; unknown unknowns; extensive-form games; normal-form games; extensive-form rationalizability; prudent rationalizability; iterated conditional dominance; iterated admissibility